2019
DOI: 10.1371/journal.pone.0213827
|View full text |Cite
|
Sign up to set email alerts
|

Success with EASE: Who benefits from a STEM learning community?

Abstract: During the past few decades, there has been a nationwide push to improve performance and persistence outcomes for STEM undergraduates. As part of this effort, recent research has emphasized the need for focus on not only improving the delivery of course content, but also addressing the social-psychological needs of students. One promising intervention type that has been proposed as a multifaceted way to address both cognitive and social-psychological aspects of the learning process is the learning community. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
(35 reference statements)
3
24
0
Order By: Relevance
“…It is possible that the significant student–student interactions implemented in the intervention course, especially in the 50-minute PLTL discussion sections, led to this increase in peer support. This would echo recent evidence that establishment of near peer–mentored learning communities promotes greater social integration of female participants (Solanki et al. , 2019).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It is possible that the significant student–student interactions implemented in the intervention course, especially in the 50-minute PLTL discussion sections, led to this increase in peer support. This would echo recent evidence that establishment of near peer–mentored learning communities promotes greater social integration of female participants (Solanki et al. , 2019).…”
Section: Discussionsupporting
confidence: 68%
“…We were interested in assessing whether the intervention course design with near peer–led discussion sections might promote increased perceptions of classroom belonging, which in turn might influence student retention (Solanki et al. , 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the community is designed to connect social and student support programs to the curriculum, relationships between faculty and students are strengthened and participants experience a greater level of engagement with campus life and academic identity (Tinto, 2003). Such psychosocial factors have been shown to be important for first year STEM students and linked to improved outcomes such as first year retention and graduation rates (Carrino & Gerace, 2016;Gillespie & Petitubin, 2016;Solanki, McPartlan, Xu, & Sato, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last twenty years, much research has suggested that learning communities have a positive effect on student outcomes for students most at risk of not graduating (Brownell & Swaner, 2009;Otto et al, 2015;Weiss et al, 2015;Zhao & Kuh, 2004), including improving their persistence in STEM (Graham et al, 2013;Dagley, Georgiopoulos, Reece, & Young, 2016;Solanki et al, 2019). However, precious little of this research involves well-controlled experimental trials.…”
Section: Introductionmentioning
confidence: 99%